A tool for the analysis of chromosomes: KaryoType. Issue 3 (1st June 2016) - Altınordu, Fahim; Peruzzi, Lorenzo; Yu, Yan; He, Xingjin
Abstract: The software KaryoType, an improved and completely renewed version of the previously existing NucType, was developed for plant chromosomes. The primary function of the software is to allow efficient chromosome measurements and karyotype analysis from microphotographs. Karyotype characterization usually includes chromosome number, size, arm ratio, centromeric index, relative lengths and karyotype formula. Moreover, KaryoType is also capable of measuring karyotype asymmetry indices such as CVCL, CVCI and MCA, and can recognize chromosome homologues based on chromosome length and arm ratio automatically or manually. This program runs on Windows 7 and above and Mac OS X and is freely available at the website of the University of Sichuan (http://mnh.scu.edu.cn/soft/blog/karyotype/).